Meghan Hickey: capstone - Hickey, Meghan, artist (Colorado State University. Libraries, 2021)
The artist's statement: My name is Meghan Hickey, and I am graphic designer from Fort Collins, Colorado, come on in let me tell you a little bit about my work. Primarily through my art I hope to work through my designs to match up themes of humor, art and usability. I strive to bring a sense of creativity, and new perspectives to a digital field. Though primarily based in text and typography, I have been working to improve and transfer my traditional art skills into a digital medium. My work is based a lot in process of thinking and creating ideas, trying as hard as I can to make sure that my work stands out visually and creatively. I love seeking new and unique solutions to creative problems. I often view my projects as puzzles, I love spending time working each piece together, often unaware myself of what the final image will be. This is one of the greatest things about creating and making art is the ability to see it at different stages of creation. Creating the bones and framework, for a work then slowly adding on piece by piece until you have a fully formed project in front of you.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design